Manganese zinc ferrite material as well as preparation method and application thereof
Through the preparation of manganese-zeb ferrite materials with specific components, the problem of existing ferrite sheets being difficult to have both thin thickness and high sensitivity is solved, and efficient isolation of magnetic fields and metal components is achieved, improving wireless charging efficiency and ensuring safety.
Patent Information
- Application Number
- CN202411672977.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing ferrite sheets are difficult to have both thin thickness and high sensitivity, and cannot effectively solve the eddy current loss problem caused by the interaction between the magnetic field and the metal components during wireless charging.
Manganese zinc ferrite materials with specific components, including 52.0 to 53.0 mol% Fe2O3, 18.0 to 19.0 mol% ZnO, 28.0 to 29.5 mol% MnO, and auxiliary components Co2O3, Bi2O3, MoO3, and MoO3, are mixed and pre-pre- Manganese-zeb ferrite material with high magnetic permeability is prepared by sintering, ball milling, granulation, casting and sintering.
The prepared manganese zinc ferrite material has high magnetic permeability and flatness, which can effectively isolate the alternating magnetic field from metal parts, reduce eddy current losses, improve wireless charging efficiency and ensure safe use.
Smart Images

Figure BDA0005146349870000141 
Figure BDA0005146349870000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ferrite materials, and in particular to a manganese-zinc ferrite material and a preparation method and application thereof. Background Art
[0002] As a fashionable and convenient charging method, wireless charging is favored and concerned by consumers, and is developing rapidly in the field of consumer electronic products such as mobile phones and tablets. However, with the widespread application of wireless charging technology in smart mobile terminal devices, the disadvantages of wireless charging devices are gradually revealed. Due to the constraints of space factors, the coil of the wireless charging receiving end must inevitably be close to metal parts such as circuit boards or batteries. As we all know, when an alternating magnetic field encounters a conductor such as a metal, if the metal is a closed wire, a current will be generated, and the current will stimulate a reverse magnetic field to reduce the original magnetic field. If the metal is a whole piece of metal, due to the influence of the metal skin effect, an eddy current effect will be generated. Eddy current heating not only consumes too much electricity, but also generates a lot of heat, which not only reduces the charging efficiency and wastes electricity, but also causes damage to electronic equipment, and even fire, explosion and other safety issues. In order to avoid the above phenomenon, improve charging efficiency and ensure safe use, the current mainstream solution is to attach a soft ferrite sheet between the wireless charging receiving coil and the metal parts. The ferrite sheet can effectively separate the alternating magnetic field from the metal parts, avoid eddy current losses, and achieve the purpose of improving wireless charging efficiency.
[0003] However, it is difficult for the ferrite sheets in the prior art to have both thin thickness and high inductance performance. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the problem that the ferrite sheets in the prior art are difficult to have both thin thickness and high inductance performance, thereby providing a manganese-zinc ferrite material and a preparation method and application thereof.
[0005] The present invention provides a manganese-zinc ferrite material, the raw materials of which include a main component and an auxiliary component;
[0006] The main components include 52.0-53.0 mol% of Fe2O3, 18.0-19.0 mol% of ZnO, and 28.0-29.5 mol% of MnO;
[0007] Based on the total weight of the main components: the auxiliary components include 100-2000 ppm Co2O3; 100-2000 ppm Bi2O3; 100-2000 ppm MoO3.
[0008] The present invention also provides a method for preparing the above-mentioned manganese-zinc ferrite material, comprising the following steps:
[0009] (1) mixing the main component and the auxiliary component in the raw materials, pre-sintering, and first ball milling to obtain a manganese-zinc ferrite mixture;
[0010] (2) mixing the manganese zinc ferrite mixture with a binder, granulating, and sieving to obtain manganese zinc ferrite precursor particles;
[0011] (3) mixing the solvent, dispersant, manganese zinc ferrite precursor particles, plasticizer, and glue, and then performing tape casting and sintering to obtain the manganese zinc ferrite material;
[0012] The main components include 52.0-53.0 mol% of Fe2O3, 18.0-19.0 mol% of ZnO, and 28.0-29.5 mol% of MnO;
[0013] Based on the total weight of the main components: the auxiliary components include 0 to 2000 ppm Co2O3; 100 to 2000 ppm Bi2O3; and 100 to 2000 ppm MoO3.
[0014] Preferably, in step (1), the pre-sintering temperature is 700-850° C.; the pre-sintering time is 2.5-3.5 h;
[0015] Preferably, the particle size of the manganese-zinc ferrite mixture is SMD 1.05-1.2 μm;
[0016] Preferably, the first ball milling time is 2-3 h.
[0017] It will be appreciated that SMD is the Sauter Mean Diameter.
[0018] Preferably, in step (2), the mass ratio of the manganese-zinc ferrite mixture to the binder is 1:(0.06-0.09);
[0019] Preferably, the adhesive comprises polyvinyl alcohol;
[0020] Preferably, the particle size of the manganese zinc ferrite precursor particles obtained after sieving is SMD3.05-5.6 μm.
[0021] Preferably, in step (3), the mass ratio of manganese zinc ferrite precursor particles, solvent, dispersant, plasticizer, and glue is (50-70): (5.5-7.5): (2.5-3.5): (3.5-4.5): (5.5-7.5);
[0022] Preferably, the process of mixing the solvent, dispersant, manganese zinc ferrite precursor particles, plasticizer and glue is to perform a second ball milling on the solvent, dispersant and manganese zinc ferrite precursor particles, and then add the plasticizer and glue to perform a third ball milling.
[0023] Preferably, the solvent is selected from at least one of methanol, ethanol and acetone;
[0024] Preferably, the dispersant is selected from at least one of triolein and fish oil;
[0025] Preferably, the plasticizer is selected from at least one of dibutyl phthalate, polyethylene glycol, and glycerol;
[0026] Preferably, the glue is selected from at least one of polymethyl methacrylate and polyvinyl butyral;
[0027] Preferably, the second ball milling time is 4-8h;
[0028] Preferably, the third ball milling time is 12-24 hours.
[0029] Preferably, the thickness of the cast sheet obtained by tape casting is 18-40 μm.
[0030] Preferably, the process of cutting is also included after tape casting and before sintering;
[0031] Preferably, the cut cast sheet is a rectangle with a length of 50-150 mm and a width of 50-150 mm;
[0032] Preferably, during the sintering process in step (3), the cast sheet is pressed on one side;
[0033] Preferably, the sintering atmosphere in step (3) comprises nitrogen and oxygen, wherein the oxygen content in the sintering atmosphere is 3 to 21 vol%;
[0034] Preferably, in step (3), the sintering temperature is 1000-1200°C;
[0035] Preferably, in step (3), the sintering process is to first heat the temperature to the first temperature, and then heat the temperature to the second temperature and keep it for 2-6 hours;
[0036] Preferably, in step (3), the first temperature is 1000-1100° C., and the second temperature is 1130-1200° C.;
[0037] Preferably, the heating rate from the first temperature to the second temperature is 1.5-3°C / min.
[0038] Preferably, in step (3), a pre-sintering process is further included after tape casting and before sintering; the pre-sintering process is pre-sintering at 550-650° C. for 2-4 hours; the pre-sintering atmosphere includes nitrogen and oxygen, wherein the oxygen content in the sintering atmosphere is 19-21 vol%;
[0039] Preferably, the heating process from the preliminary sintering temperature to the first temperature is 6-8 hours; the atmosphere during the heating process is nitrogen.
[0040] Preferably, step (3) further includes a cooling process after sintering, and the cooling process is carried out under a balanced oxygen partial pressure.
[0041] The present invention further provides a wireless charging device, wherein the wireless charging device comprises the manganese-zinc ferrite material described above or the manganese-zinc ferrite material prepared by the method for preparing the manganese-zinc ferrite material described above.
[0042] The technical solution of the present invention has the following advantages:
[0043] The present invention provides a manganese-zinc ferrite material, wherein the raw materials include a main component and an auxiliary component; the main component includes 52.0-53.0 mol% of Fe2O3, 18.0-19.0 mol% of ZnO, and 28.0-29.5 mol% of MnO; based on the total weight of the main component: the auxiliary components include 100-2000 ppm of Co2O3; 100-2000 ppm of Bi2O3; and 100-2000 ppm of MoO3.
[0044] In the present invention, by limiting the main components to Fe2O3, ZnO, MnO and the auxiliary components to Co2O3, Bi2O3, MoO3 and limiting the relative content of each component, the manganese-zinc ferrite material finally prepared has a higher magnetic permeability;
[0045] The present invention further provides a method for preparing a manganese-zinc ferrite material, comprising the following steps:
[0046] (1) mixing the main component and the auxiliary component in the raw materials, pre-sintering, and first ball milling to obtain a manganese-zinc ferrite mixture;
[0047] (2) mixing the manganese-zinc ferrite mixture with a binder, granulating and screening to obtain manganese-zinc ferrite precursor particles; (3) mixing a solvent, a dispersant, the manganese-zinc ferrite precursor particles, a plasticizer and glue, and then performing tape casting and sintering to obtain the manganese-zinc ferrite material; wherein the main components include 52.0-53.0 mol% of Fe2O3, 18.0-19.0 mol% of ZnO, and 28.0-29.5 mol% of MnO; based on the total weight of the main components: the auxiliary components include 0-2000 ppm of Co2O3; 100-2000 ppm of Bi2O3; and 100-2000 ppm of MoO3.
[0048] In the present invention, on the basis of determining the composition, by selecting a specific preparation method, the thickness of the final tape-cast manganese-zinc ferrite material can be as high as 18 μm, and the cut has a higher flatness and a higher magnetic permeability, and can be better used in wireless charging devices. DETAILED DESCRIPTION
[0049] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0050] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0051] The viscosity of the polyvinyl butyral used in the examples and comparative examples is 20 to 35 cP·s;
[0052] The molecular weight of the polyvinyl alcohol PVA used in the examples and comparative examples is 13,000-23,000.
[0053] Example 1
[0054] This embodiment provides a manganese-zinc ferrite material, and the preparation method includes the following steps:
[0055] (1) Weigh the main components of the raw materials (including Fe2O3: 52.27 mol%, MnO: 29.21 mol%, ZnO: 18.52 mol%), and weigh the auxiliary components: Bi2O3: 400 ppm, MoO3: 200 ppm, Co2O3: 1200 ppm based on the total weight of the main components of the raw materials;
[0056] (2) The main component and the auxiliary component of the raw material are ball-milled in a ball mill for 30 minutes and then dried, and then sintered at 820° C. for 3 hours and then horizontally ball-milled for 2.2 hours (wherein the ball milling abrasive is zirconium dioxide, and the abrasive is divided into large balls and small balls, the diameter of the large ball is 15 mm, the diameter of the small ball is 5 mm, and the mass ratio of the two is 2:1) to obtain a manganese-zinc ferrite mixture (particle size SMD 1.05-1.2 μm);
[0057] (3) The manganese zinc ferrite mixture obtained above and the PVA material are mixed in a weight ratio of 1:0.08, and then granulated and sieved to obtain manganese zinc ferrite precursor particles with a particle size of SMD 3.05-5.0 μm;
[0058] (4) weighing manganese zinc ferrite precursor particles, ethanol (solvent), triolein (dispersant), dibutyl phthalate (plasticizer), and polyvinyl butyral (glue) in a weight ratio of 60:6:3:4:6; mixing the weighed solvent and dispersant with the manganese zinc ferrite precursor particles and zirconium balls for 8 hours, then adding the weighed plasticizer and glue and continuing to ball mill for 15 hours, and then casting into a 18 μm cast sheet, which was then cut into 10 0mm*100mm slices; press one side of the slices at 600℃ in an atmosphere with a nitrogen and oxygen volume ratio of (79:21) for 4 hours, then heat it to 1000℃ in a nitrogen atmosphere for 8 hours, then heat it to 1160℃ at a heating rate of 2℃ / min in an atmosphere with a nitrogen and oxygen volume ratio of (94:6) and sinter it at this atmosphere and temperature for 6 hours, and then cool it under equilibrium oxygen partial pressure to obtain manganese-zinc ferrite material.
[0059] Example 2
[0060] This embodiment provides a manganese-zinc ferrite material, and the preparation method includes the following steps:
[0061] (1) Weigh the main components of the raw materials (including Fe2O3: 52.26 mol%, MnO: 29.34 mol%, ZnO: 18.4 mol%), and weigh the auxiliary components: Bi2O3: 400 ppm, MoO3: 200 ppm, Co2O3: 1000 ppm based on the total weight of the main components of the raw materials;
[0062] (2) The main component and the auxiliary component of the raw material are ball-milled in a ball mill for 30 minutes and then dried, and then sintered at 820° C. for 3 hours and then horizontally ball-milled for 2.2 hours (wherein the ball milling abrasive is zirconium dioxide, and the abrasive is divided into large balls and small balls, the diameter of the large ball is 15 mm, the diameter of the small ball is 5 mm, and the mass ratio of the two is 2:1) to obtain a manganese-zinc ferrite mixture (particle size SMD 1.05-1.2 μm);
[0063] (3) The manganese zinc ferrite mixture obtained above and the PVA material are mixed in a weight ratio of 1:0.08, and then granulated and sieved to obtain manganese zinc ferrite precursor particles with a particle size of SMD 3.05-5.0 μm;
[0064] (4) weighing manganese zinc ferrite precursor particles, ethanol (solvent), triolein (dispersant), dibutyl phthalate (plasticizer), and polyvinyl butyral (glue) in a weight ratio of 60:6:3:4:6; mixing the weighed solvent and dispersant with the manganese zinc ferrite precursor particles and zirconium balls for 8 hours, then adding the weighed plasticizer and glue and continuing to ball mill for 15 hours, and then casting into a 18 μm cast sheet, which was then cut into 10 0mm*100mm slices; press one side of the slices at 600℃ in an atmosphere with a nitrogen and oxygen volume ratio of (79:21) for 4 hours, then heat it to 1000℃ in a nitrogen atmosphere for 8 hours, then heat it to 1160℃ at a heating rate of 2℃ / min in an atmosphere with a nitrogen and oxygen volume ratio of (94:6) and sinter it at this atmosphere and temperature for 6 hours, and then cool it under equilibrium oxygen partial pressure to obtain manganese-zinc ferrite material.
[0065] Example 3
[0066] This embodiment provides a manganese-zinc ferrite material, and the preparation method includes the following steps:
[0067] (1) Weigh the main components of the raw materials (including Fe2O3: 52.5 mol%, MnO: 29 mol%, ZnO: 18.5 mol%), and weigh the auxiliary components: Bi2O3: 400 ppm, MoO3: 200 ppm, Co2O3: 1500 ppm based on the total weight of the main components of the raw materials;
[0068] (2) The main component and the auxiliary component of the raw material are ball-milled in a ball mill for 30 minutes and then dried, and then sintered at 850° C. for 3 hours and then horizontally ball-milled for 3 hours (wherein the ball milling abrasive is zirconium dioxide, and the abrasive is divided into large balls and small balls, the diameter of the large ball is 15 mm, the diameter of the small ball is 5 mm, and the mass ratio of the two is 2:1) to obtain a manganese-zinc ferrite mixture (particle size is SMD1.05-1.2 μm);
[0069] (3) The manganese zinc ferrite mixture obtained above and the PVA material are mixed in a weight ratio of 1:0.08, and then granulated and sieved to obtain manganese zinc ferrite precursor particles with a particle size of SMD 3.05-5.0 μm;
[0070] (4) weighing manganese zinc ferrite precursor particles, ethanol (solvent), triolein (dispersant), dibutyl phthalate (plasticizer), and polyvinyl butyral (glue) in a weight ratio of 50:6:3:4:7; mixing the weighed solvent and dispersant with the manganese zinc ferrite precursor particles and zirconium balls for 8 hours, then adding the weighed plasticizer and glue and continuing to ball mill for 15 hours, and then casting into 18 μm cast sheets, which were then cut into 10 0mm*100mm slices; press one side of the slices at 600℃ in an atmosphere with a nitrogen and oxygen volume ratio of (79:21) for 4 hours, then heat it to 1000℃ in a nitrogen atmosphere for 8 hours, then heat it to 1160℃ at a heating rate of 2℃ / min in an atmosphere with a nitrogen and oxygen volume ratio of (94:6) and sinter it at this atmosphere and temperature for 6 hours, and then cool it under equilibrium oxygen partial pressure to obtain manganese-zinc ferrite material.
[0071] Example 4
[0072] This embodiment provides a manganese-zinc ferrite material, and the preparation method includes the following steps:
[0073] (1) Weigh the main components of the raw materials (including Fe2O3: 52.5 mol%, MnO: 29 mol%, ZnO: 18.5 mol%), and weigh the auxiliary components: Bi2O3: 200 ppm, MoO3: 100 ppm, Co2O3: 2000 ppm based on the total weight of the main components of the raw materials;
[0074] (2) The main component and the auxiliary component of the raw material are ball-milled in a ball mill for 30 minutes and then dried, and then sintered at 700°C for 3.5 hours and then horizontally ball-milled for 2 hours (wherein the ball milling abrasive is zirconium dioxide, and the abrasive is divided into large balls and small balls, the diameter of the large ball is 15 mm, the diameter of the small ball is 5 mm, and the mass ratio of the two is 2:1) to obtain a manganese-zinc ferrite mixture (particle size SMD 1.05-1.2 μm);
[0075] (3) The manganese zinc ferrite mixture obtained above and the PVA material are mixed in a weight ratio of 1:0.08, and then granulated and sieved to obtain manganese zinc ferrite precursor particles with a particle size of SMD 3.05-5.0 μm;
[0076] (4) weighing manganese zinc ferrite precursor particles, ethanol (solvent), triolein (dispersant), dibutyl phthalate (plasticizer), and polyvinyl butyral (glue) in a weight ratio of 60:6:3:4:6; mixing the weighed solvent and dispersant with the manganese zinc ferrite precursor particles and zirconium balls for 8 hours, then adding the weighed plasticizer and glue and continuing to ball mill for 15 hours, and then casting into a 18 μm cast sheet, which was then cut into 10 0mm*100mm slices; press one side of the slices at 600℃ in an atmosphere with a nitrogen and oxygen volume ratio of (79:21) for 4 hours, then heat it to 1000℃ in a nitrogen atmosphere for 8 hours, then heat it to 1200℃ in an atmosphere with a nitrogen and oxygen volume ratio of (90:10) at a heating rate of 2℃ / min and sinter it at this atmosphere and temperature for 6 hours, and then cool it under equilibrium oxygen partial pressure to obtain manganese-zinc ferrite material.
[0077] Example 5
[0078] This embodiment provides a manganese-zinc ferrite material, and the preparation method includes the following steps:
[0079] (1) Weigh the main components of the raw materials (including Fe2O3: 52.28 mol%, MnO: 29 mol%, ZnO: 18.72 mol%), and weigh the auxiliary components: Bi2O3: 400 ppm, MoO3: 200 ppm, Co2O3: 200 ppm based on the total weight of the main components of the raw materials;
[0080] (2) The main component and the auxiliary component of the raw material are ball-milled in a ball mill for 30 minutes and then dried, and then sintered at 700°C for 3.5 hours and then horizontally ball-milled for 2 hours (wherein the ball milling abrasive is zirconium dioxide, and the abrasive is divided into large balls and small balls, the diameter of the large ball is 15 mm, the diameter of the small ball is 5 mm, and the mass ratio of the two is 2:1) to obtain a manganese-zinc ferrite mixture (particle size SMD 1.05-1.2 μm);
[0081] (3) The manganese zinc ferrite mixture obtained above and the PVA material are mixed in a weight ratio of 1:0.08, and then granulated and sieved to obtain manganese zinc ferrite precursor particles with a particle size of SMD 3.05-5.0 μm;
[0082] (4) weighing manganese zinc ferrite precursor particles, ethanol (solvent), triolein (dispersant), dibutyl phthalate (plasticizer), and polyvinyl butyral (glue) in a weight ratio of 60:6:3:4:6; mixing the weighed solvent and dispersant with the manganese zinc ferrite precursor particles and zirconium balls for 8 hours, then adding the weighed plasticizer and glue and continuing to ball mill for 15 hours, and then casting into a 18 μm cast sheet, which was then cut into 10 0mm*100mm slices; press one side of the slices at 600℃ in an atmosphere with a nitrogen and oxygen volume ratio of (79:21) for 4 hours, then heat it to 1000℃ in a nitrogen atmosphere for 8 hours, then heat it to 1200℃ in an atmosphere with a nitrogen and oxygen volume ratio of (90:10) at a heating rate of 2℃ / min and sinter it at this atmosphere and temperature for 6 hours, and then cool it under equilibrium oxygen partial pressure to obtain manganese-zinc ferrite material.
[0083] Example 6
[0084] This embodiment provides a manganese-zinc ferrite material, and the preparation method includes the following steps:
[0085] (1) Weigh the main components of the raw materials (including Fe2O3: 52.5 mol%, MnO: 29.34 mol%, ZnO: 18.16 mol%), and weigh the auxiliary components: Bi2O3: 1000 ppm, MoO3: 400 ppm, Co2O3: 200 ppm based on the total weight of the main components of the raw materials;
[0086] (2) The main component and the auxiliary component of the raw material are ball-milled in a ball mill for 30 minutes and then dried, and then sintered at 700°C for 3.5 hours and then horizontally ball-milled for 2 hours (wherein the ball milling abrasive is zirconium dioxide, and the abrasive is divided into large balls and small balls, the diameter of the large ball is 15 mm, the diameter of the small ball is 5 mm, and the mass ratio of the two is 2:1) to obtain a manganese-zinc ferrite mixture (particle size SMD 1.05-1.2 μm);
[0087] (3) The manganese zinc ferrite mixture obtained above and the PVA material are mixed in a weight ratio of 1:0.08, and then granulated and sieved to obtain manganese zinc ferrite precursor particles with a particle size of SMD 3.05-5.0 μm;
[0088] (4) weighing manganese zinc ferrite precursor particles, ethanol (solvent), triolein (dispersant), dibutyl phthalate (plasticizer), and polyvinyl butyral (glue) in a weight ratio of 60:6:3:4:6; mixing the weighed solvent and dispersant with the manganese zinc ferrite precursor particles and zirconium balls for 8 hours, then adding the weighed plasticizer and glue and continuing to ball mill for 15 hours, and then casting into a 18 μm cast sheet, which was then cut into 10 0mm*100mm slices; press one side of the slices at 600℃ in an atmosphere with a nitrogen and oxygen volume ratio of (79:21) for 4 hours, then heat it to 1000℃ in a nitrogen atmosphere for 8 hours, then heat it to 1200℃ in an atmosphere with a nitrogen and oxygen volume ratio of (90:10) at a heating rate of 2℃ / min and sinter it at this atmosphere and temperature for 6 hours, and then cool it under equilibrium oxygen partial pressure to obtain manganese-zinc ferrite material.
[0089] Comparative Example 1
[0090] This comparative example provides a manganese-zinc ferrite material, and the preparation method comprises the following steps:
[0091] (1) Weigh the main components of the raw materials (including Fe2O3: 52.74 mol%, MnO: 26.97 mol%, ZnO: 20.29 mol%), and weigh the auxiliary component Bi2O3: 100 ppm based on the total weight of the main components of the raw materials;
[0092] (2) The main component and the auxiliary component of the raw material are ball-milled in a ball mill for 30 minutes and then dried, and then sintered at 820° C. for 3 hours and then horizontally ball-milled for 2.2 hours (wherein the ball milling abrasive is zirconium dioxide, and the abrasive is divided into large balls and small balls, the diameter of the large ball is 15 mm, the diameter of the small ball is 5 mm, and the mass ratio of the two is 2:1) to obtain a manganese-zinc ferrite mixture (particle size SMD 1.05-1.2 μm);
[0093] (3) The manganese zinc ferrite mixture obtained above and the PVA material are mixed in a weight ratio of 1:0.08, and then granulated and sieved to obtain manganese zinc ferrite precursor particles with a particle size of SMD 3.05-5.0 μm;
[0094] (4) weighing manganese zinc ferrite precursor particles, ethanol (solvent), triolein (dispersant), dibutyl phthalate (plasticizer), and polyvinyl butyral (glue) in a weight ratio of 60:6:3:4:6; mixing the weighed solvent and dispersant with the manganese zinc ferrite precursor particles and zirconium balls for 8 hours, then adding the weighed plasticizer and glue and continuing to ball mill for 15 hours, and then casting into a 18 μm cast sheet, which was then cut into 10 0mm*100mm slices; press one side of the slices at 600℃ in an atmosphere with a nitrogen and oxygen volume ratio of (79:21) for 4 hours, then heat it to 1000℃ in a nitrogen atmosphere for 8 hours, then heat it to 1160℃ at a heating rate of 2℃ / min in an atmosphere with a nitrogen and oxygen volume ratio of (94:6) and sinter it at this atmosphere and temperature for 6 hours, and then cool it under equilibrium oxygen partial pressure to obtain manganese-zinc ferrite material.
[0095] Comparative Example 2
[0096] This comparative example provides a manganese-zinc ferrite material, and the preparation method comprises the following steps:
[0097] (1) Weigh the main components of the raw materials (including Fe2O3: 52.5 mol%, MnO: 24.5 mol%, ZnO: 23 mol%), and weigh the auxiliary components: Bi2O3: 200 ppm, MoO3: 200 ppm based on the total weight of the main components of the raw materials;
[0098] (2) The main component and the auxiliary component of the raw material are ball-milled in a ball mill for 30 minutes and then dried, and then sintered at 820° C. for 3 hours and then horizontally ball-milled for 2.2 hours (wherein the ball milling abrasive is zirconium dioxide, and the abrasive is divided into large balls and small balls, the diameter of the large ball is 15 mm, the diameter of the small ball is 5 mm, and the mass ratio of the two is 2:1) to obtain a manganese-zinc ferrite mixture (particle size SMD 1.05-1.2 μm);
[0099] (3) The manganese zinc ferrite mixture obtained above and the PVA material are mixed in a weight ratio of 1:0.08, and then granulated and sieved to obtain manganese zinc ferrite precursor particles with a particle size of SMD 3.05-5.0 μm;
[0100] (4) weighing manganese zinc ferrite precursor particles, ethanol (solvent), triolein (dispersant), dibutyl phthalate (plasticizer), and polyvinyl butyral (glue) in a weight ratio of 60:6:3:4:6; mixing the weighed solvent and dispersant with the manganese zinc ferrite precursor particles and zirconium balls for 8 hours, then adding the weighed plasticizer and glue and continuing to ball mill for 15 hours, and then casting into a 18 μm cast sheet, which was then cut into 10 0mm*100mm slices; press one side of the slices at 600℃ in an atmosphere with a nitrogen and oxygen volume ratio of (79:21) for 4 hours, then heat it to 1000℃ in a nitrogen atmosphere for 8 hours, then heat it to 1160℃ at a heating rate of 2℃ / min in an atmosphere with a nitrogen and oxygen volume ratio of (94:6) and sinter it at this atmosphere and temperature for 6 hours, and then cool it under equilibrium oxygen partial pressure to obtain manganese-zinc ferrite material.
[0101] Comparative Example 3
[0102] This comparative example provides a manganese-zinc ferrite material, and the preparation method comprises the following steps:
[0103] (1) Weigh the main components of the raw materials (including Fe2O3: 52.8 mol%, MnO: 21.5 mol%, ZnO: 25.7 mol%), and weigh the auxiliary components: Bi2O3: 400 ppm, MoO3: 200 ppm based on the total weight of the main components of the raw materials;
[0104] (2) The main component and the auxiliary component of the raw material are ball-milled in a ball mill for 30 minutes and then dried, and then sintered at 820° C. for 3 hours and then horizontally ball-milled for 2.2 hours (wherein the ball milling abrasive is zirconium dioxide, and the abrasive is divided into large balls and small balls, the diameter of the large ball is 15 mm, the diameter of the small ball is 5 mm, and the mass ratio of the two is 2:1) to obtain a manganese-zinc ferrite mixture (particle size is 1.05-1.2 μm);
[0105] (3) The manganese zinc ferrite mixture obtained above and the PVA material are mixed in a weight ratio of 1:0.08, and then granulated and sieved to obtain manganese zinc ferrite precursor particles with a particle size of SMD 3.05-5.0 μm;
[0106] (4) weighing manganese zinc ferrite precursor particles, ethanol (solvent), triolein (dispersant), dibutyl phthalate (plasticizer), and polyvinyl butyral (glue) in a weight ratio of 60:6:3:4:6; mixing the weighed solvent and dispersant with the manganese zinc ferrite precursor particles and zirconium balls for 8 hours, then adding the weighed plasticizer and glue and continuing to ball mill for 15 hours, and then casting into a 18 μm cast sheet, which was then cut into 10 0mm*100mm slices; press one side of the slices at 600℃ in an atmosphere with a nitrogen and oxygen volume ratio of (79:21) for 4 hours, then heat it to 1000℃ in a nitrogen atmosphere for 8 hours, then heat it to 1160℃ at a heating rate of 2℃ / min in an atmosphere with a nitrogen and oxygen volume ratio of (94:6) and sinter it at this atmosphere and temperature for 6 hours, and then cool it under equilibrium oxygen partial pressure to obtain manganese-zinc ferrite material.
[0107] Comparative Example 4
[0108] This comparative example provides a manganese-zinc ferrite material, and the preparation method comprises the following steps:
[0109] (1) Weigh the main components of the raw materials (including Fe2O3: 52.27 mol%, MnO: 26.97 mol%, ZnO: 20.76 mol%), and weigh the auxiliary components: Bi2O3: 400 ppm, MoO3: 200 ppm, Co2O3: 1200 ppm based on the total weight of the main components of the raw materials;
[0110] (2) The main component and the auxiliary component of the raw material are ball-milled in a ball mill for 30 minutes and then dried, and then sintered at 820° C. for 3 hours and then horizontally ball-milled for 2.2 hours (wherein the ball milling abrasive is zirconium dioxide, and the abrasive is divided into large balls and small balls, the diameter of the large ball is 15 mm, the diameter of the small ball is 5 mm, and the mass ratio of the two is 2:1) to obtain a manganese-zinc ferrite mixture (particle size is 1.05-1.2 μm);
[0111] (3) The manganese zinc ferrite mixture obtained above and the PVA material are mixed in a weight ratio of 1:0.08, and then granulated and sieved to obtain manganese zinc ferrite precursor particles with a particle size of SMD 3.05-5.0 μm;
[0112] (4) weighing manganese zinc ferrite precursor particles, ethanol (solvent), triolein (dispersant), dibutyl phthalate (plasticizer), and polyvinyl butyral (glue) in a weight ratio of 60:6:3:4:6; mixing the weighed solvent and dispersant with the manganese zinc ferrite precursor particles and zirconium balls for 8 hours, then adding the weighed plasticizer and glue and continuing to ball mill for 15 hours, and then casting into a 18 μm cast sheet, which was then cut into 10 0mm*100mm slices; press one side of the slices at 600℃ in an atmosphere with a nitrogen and oxygen volume ratio of (79:21) for 4 hours, then heat it to 1000℃ in a nitrogen atmosphere for 8 hours, then heat it to 1160℃ at a heating rate of 2℃ / min in an atmosphere with a nitrogen and oxygen volume ratio of (94:6) and sinter it at this atmosphere and temperature for 6 hours, and then cool it under equilibrium oxygen partial pressure to obtain manganese-zinc ferrite material.
[0113] Comparative Example 5
[0114] This embodiment provides a manganese-zinc ferrite material, and the preparation method includes the following steps:
[0115] (1) Weigh the main components of the raw materials (including Fe2O3: 51 mol%, MnO: 29.21 mol%, ZnO: 19.79 mol%), and weigh the auxiliary components: Bi2O3: 400 ppm, MoO3: 200 ppm, Co2O3: 1200 ppm based on the total weight of the main components of the raw materials;
[0116] (2) The main component and the auxiliary component of the raw material are ball-milled in a ball mill for 30 minutes and then dried, and then sintered at 820°C for 3 hours and then horizontally ball-milled for 2.2 hours (wherein the ball milling abrasive is zirconium dioxide, and the abrasive is divided into large balls and small balls, the diameter of the large ball is 15 mm, the diameter of the small ball is 5 mm, and the mass ratio of the two is 2:1) to obtain a manganese-zinc ferrite mixture (particle size is SMD1.05-1.2μm);
[0117] (3) The manganese zinc ferrite mixture obtained above and the PVA material are mixed in a weight ratio of 1:0.08, and then granulated and sieved to obtain manganese zinc ferrite precursor particles with a particle size of SMD 3.05-5.0 μm;
[0118] (4) weighing manganese zinc ferrite precursor particles, ethanol (solvent), triolein (dispersant), dibutyl phthalate (plasticizer), and polyvinyl butyral (glue) in a weight ratio of 60:6:3:4:6; mixing the weighed solvent and dispersant with the manganese zinc ferrite precursor particles and zirconium balls for 8 hours, then adding the weighed plasticizer and glue and continuing to ball mill for 15 hours, and then casting into a 18 μm cast sheet, which was then cut into 10 0mm*100mm slices; press one side of the slices at 600℃ in an atmosphere with a nitrogen and oxygen volume ratio of (79:21) for 4 hours, then heat it to 1000℃ in a nitrogen atmosphere for 8 hours, then heat it to 1160℃ at a heating rate of 2℃ / min in an atmosphere with a nitrogen and oxygen volume ratio of (94:6) and sinter it at this atmosphere and temperature for 6 hours, and then cool it under equilibrium oxygen partial pressure to obtain manganese-zinc ferrite material.
[0119] Comparative Example 6
[0120] This embodiment provides a manganese-zinc ferrite material, and the preparation method includes the following steps:
[0121] (1) Weigh the main components of the raw materials (including Fe2O3: 52.27 mol%, MnO: 29.21 mol%, ZnO: 18.52 mol%), and weigh the auxiliary components: Bi2O3: 1200 ppm, MoO3: 600 ppm based on the total weight of the main components of the raw materials;
[0122] (2) The main component and the auxiliary component of the raw material are ball-milled in a ball mill for 30 minutes and then dried, and then sintered at 820°C for 3 hours and then horizontally ball-milled for 2.2 hours (wherein the ball milling abrasive is zirconium dioxide, and the abrasive is divided into large balls and small balls, the diameter of the large ball is 15 mm, the diameter of the small ball is 5 mm, and the mass ratio of the two is 2:1) to obtain a manganese-zinc ferrite mixture (particle size is SMD1.05-1.2μm);
[0123] (3) The manganese zinc ferrite mixture obtained above and the PVA material are mixed in a weight ratio of 1:0.08, and then granulated and sieved to obtain manganese zinc ferrite precursor particles with a particle size of SMD 3.05-5.0 μm;
[0124] (4) weighing manganese zinc ferrite precursor particles, ethanol (solvent), triolein (dispersant), dibutyl phthalate (plasticizer), and polyvinyl butyral (glue) in a weight ratio of 60:6:3:4:6; mixing the weighed solvent and dispersant with the manganese zinc ferrite precursor particles and zirconium balls for 8 hours, then adding the weighed plasticizer and glue and continuing to ball mill for 15 hours, and then casting into a 18 μm cast sheet, which was then cut into 10 0mm*100mm slices; press one side of the slices at 600℃ in an atmosphere with a nitrogen and oxygen volume ratio of (79:21) for 4 hours, then heat it to 1000℃ in a nitrogen atmosphere for 8 hours, then heat it to 1160℃ at a heating rate of 2℃ / min in an atmosphere with a nitrogen and oxygen volume ratio of (94:6) and sinter it at this atmosphere and temperature for 6 hours, and then cool it under equilibrium oxygen partial pressure to obtain manganese-zinc ferrite material.
[0125] Comparative Example 7
[0126] This embodiment provides a manganese-zinc ferrite material, and the preparation method includes the following steps:
[0127] (1) Weigh the main components of the raw materials (including Fe2O3: 52.27 mol%, MnO: 29.21 mol%, ZnO: 18.52 mol%), and weigh the auxiliary components: MoO3: 257 ppm, Co2O3: 1543 ppm based on the total weight of the main components of the raw materials;
[0128] (2) The main component and the auxiliary component of the raw material are ball-milled in a ball mill for 30 minutes and then dried, and then sintered at 820°C for 3 hours and then horizontally ball-milled for 2.2 hours (wherein the ball milling abrasive is zirconium dioxide, and the abrasive is divided into large balls and small balls, the diameter of the large ball is 15 mm, the diameter of the small ball is 5 mm, and the mass ratio of the two is 2:1) to obtain a manganese-zinc ferrite mixture (particle size is SMD1.05-1.2μm);
[0129] (3) The manganese zinc ferrite mixture obtained above and the PVA material are mixed in a weight ratio of 1:0.08, and then granulated and sieved to obtain manganese zinc ferrite precursor particles with a particle size of SMD 3.05-5.0 μm;
[0130] (4) weighing manganese zinc ferrite precursor particles, ethanol (solvent), triolein (dispersant), dibutyl phthalate (plasticizer), and polyvinyl butyral (glue) in a weight ratio of 60:6:3:4:6; mixing the weighed solvent and dispersant with the manganese zinc ferrite precursor particles and zirconium balls for 8 hours, then adding the weighed plasticizer and glue and continuing to ball mill for 15 hours, and then casting into a 18 μm cast sheet, which was then cut into 10 0mm*100mm slices; press one side of the slices at 600℃ in an atmosphere with a nitrogen and oxygen volume ratio of (79:21) for 4 hours, then heat it to 1000℃ in a nitrogen atmosphere for 8 hours, then heat it to 1160℃ at a heating rate of 2℃ / min in an atmosphere with a nitrogen and oxygen volume ratio of (94:6) and sinter it at this atmosphere and temperature for 6 hours, and then cool it under equilibrium oxygen partial pressure to obtain manganese-zinc ferrite material.
[0131] Comparative Example 8
[0132] This comparative example provides a manganese-zinc ferrite material, and the preparation method comprises the following steps:
[0133] (1) Weigh the main components of the raw materials (including Fe2O3: 52.27 mol%, MnO: 29.21 mol%, ZnO: 18.52 mol%), and weigh the auxiliary components: Bi2O3: 450 ppm, Co2O3: 1350 ppm based on the total weight of the main components of the raw materials;
[0134] (2) The main component and the auxiliary component of the raw material are ball-milled in a ball mill for 30 minutes and then dried, and then sintered at 820°C for 3 hours and then horizontally ball-milled for 2.2 hours (wherein the ball milling abrasive is zirconium dioxide, and the abrasive is divided into large balls and small balls, the diameter of the large ball is 15 mm, the diameter of the small ball is 5 mm, and the mass ratio of the two is 2:1) to obtain a manganese-zinc ferrite mixture (particle size is SMD1.05-1.2μm);
[0135] (3) The manganese zinc ferrite mixture obtained above and the PVA material are mixed in a weight ratio of 1:0.08, and then granulated and sieved to obtain manganese zinc ferrite precursor particles with a particle size of SMD 3.05-5.0 μm;
[0136] (4) weighing manganese zinc ferrite precursor particles, ethanol (solvent), triolein (dispersant), dibutyl phthalate (plasticizer), and polyvinyl butyral (glue) in a weight ratio of 60:6:3:4:6; mixing the weighed solvent and dispersant with the manganese zinc ferrite precursor particles and zirconium balls for 8 hours, then adding the weighed plasticizer and glue and continuing to ball mill for 15 hours, and then casting into a 18 μm cast sheet, which was then cut into 10 0mm*100mm slices; press one side of the slices at 600℃ in an atmosphere with a nitrogen and oxygen volume ratio of (79:21) for 4 hours, then heat it to 1000℃ in a nitrogen atmosphere for 8 hours, then heat it to 1160℃ at a heating rate of 2℃ / min in an atmosphere with a nitrogen and oxygen volume ratio of (94:6) and sinter it at this atmosphere and temperature for 6 hours, and then cool it under equilibrium oxygen partial pressure to obtain manganese-zinc ferrite material.
[0137] Comparative Example 9
[0138] This comparative example provides a manganese-zinc ferrite material, and the preparation method comprises the following steps:
[0139] (1) Weigh the main components of the raw materials (including Fe2O3: 52.27 mol%, MnO: 29.21 mol%, ZnO: 18.52 mol%), and weigh the auxiliary components: Bi2O3: 2200 ppm, MoO3: 200 ppm, Co2O3: 1200 ppm based on the total weight of the main components of the raw materials;
[0140] (2) The main component and the auxiliary component of the raw material are ball-milled in a ball mill for 30 minutes and then dried, and then sintered at 820°C for 3 hours and then horizontally ball-milled for 2.2 hours (wherein the ball milling abrasive is zirconium dioxide, and the abrasive is divided into large balls and small balls, the diameter of the large ball is 15 mm, the diameter of the small ball is 5 mm, and the mass ratio of the two is 2:1) to obtain a manganese-zinc ferrite mixture (particle size is SMD1.05-1.2μm);
[0141] (3) The manganese zinc ferrite mixture obtained above and the PVA material are mixed in a weight ratio of 1:0.08, and then granulated and sieved to obtain manganese zinc ferrite precursor particles with a particle size of SMD 3.05-5.0 μm;
[0142] (4) weighing manganese zinc ferrite precursor particles, ethanol (solvent), triolein (dispersant), dibutyl phthalate (plasticizer), and polyvinyl butyral (glue) in a weight ratio of 60:6:3:4:6; mixing the weighed solvent and dispersant with the manganese zinc ferrite precursor particles and zirconium balls for 8 hours, then adding the weighed plasticizer and glue and continuing to ball mill for 15 hours, and then casting into a 18 μm cast sheet, which was then cut into 10 0mm*100mm slices; press one side of the slices at 600℃ in an atmosphere with a nitrogen and oxygen volume ratio of (79:21) for 4 hours, then heat it to 1000℃ in a nitrogen atmosphere for 8 hours, then heat it to 1160℃ at a heating rate of 2℃ / min in an atmosphere with a nitrogen and oxygen volume ratio of (94:6) and sinter it at this atmosphere and temperature for 6 hours, and then cool it under equilibrium oxygen partial pressure to obtain manganese-zinc ferrite material.
[0143] Comparative Example 10
[0144] This comparative example provides a manganese-zinc ferrite material, and the preparation method comprises the following steps:
[0145] (1) Weigh the main components of the raw materials (including Fe2O3: 52.27 mol%, MnO: 29.21 mol%, ZnO: 18.52 mol%), and weigh the auxiliary components: Bi2O3: 400 ppm, MoO3: 2200 ppm, Co2O3: 1200 ppm based on the total weight of the main components of the raw materials;
[0146] (2) The main component and the auxiliary component of the raw material are ball-milled in a ball mill for 30 minutes and then dried, and then sintered at 820°C for 3 hours and then horizontally ball-milled for 2.2 hours (wherein the ball milling abrasive is zirconium dioxide, and the abrasive is divided into large balls and small balls, the diameter of the large ball is 15 mm, the diameter of the small ball is 5 mm, and the mass ratio of the two is 2:1) to obtain a manganese-zinc ferrite mixture (particle size is SMD1.05-1.2μm);
[0147] (3) The manganese zinc ferrite mixture obtained above and the PVA material are mixed in a weight ratio of 1:0.08, and then granulated and sieved to obtain manganese zinc ferrite precursor particles with a particle size of SMD 3.05-5.0 μm;
[0148] (4) weighing manganese zinc ferrite precursor particles, ethanol (solvent), triolein (dispersant), dibutyl phthalate (plasticizer), and polyvinyl butyral (glue) in a weight ratio of 60:6:3:4:6; mixing the weighed solvent and dispersant with the manganese zinc ferrite precursor particles and zirconium balls for 8 hours, then adding the weighed plasticizer and glue and continuing to ball mill for 15 hours, and then casting into a 18 μm cast sheet, which was then cut into 10 0mm*100mm slices; press one side of the slices at 600℃ in an atmosphere with a nitrogen and oxygen volume ratio of (79:21) for 4 hours, then heat it to 1000℃ in a nitrogen atmosphere for 8 hours, then heat it to 1160℃ at a heating rate of 2℃ / min in an atmosphere with a nitrogen and oxygen volume ratio of (94:6) and sinter it at this atmosphere and temperature for 6 hours, and then cool it under equilibrium oxygen partial pressure to obtain manganese-zinc ferrite material.
[0149] Comparative Example 11
[0150] This comparative example provides a manganese-zinc ferrite material, and the preparation method comprises the following steps:
[0151] (1) Weighing the main components of the raw materials (including Fe2O3: 52.27 mol%, MnO: 29.21 mol%, ZnO: 18.52 mol%);
[0152] (2) The main components of the raw materials were ball-milled in a ball mill for 30 minutes and then dried, and then sintered at 820° C. for 3 hours and then horizontally ball-milled for 2.2 hours (wherein the ball milling abrasive was zirconium dioxide, and the abrasive was divided into large balls and small balls, the diameter of the large balls was 15 mm, the diameter of the small balls was 5 mm, and the mass ratio of the two was 2:1), to obtain a manganese-zinc ferrite mixture (particle size SMD1.05-1.2 μm);
[0153] (3) The manganese zinc ferrite mixture obtained above and the PVA material are mixed in a weight ratio of 1:0.08, and then granulated and sieved to obtain manganese zinc ferrite precursor particles with a particle size of SMD 3.05-5.0 μm;
[0154] (4) weighing manganese zinc ferrite precursor particles, ethanol (solvent), triolein (dispersant), dibutyl phthalate (plasticizer), and polyvinyl butyral (glue) in a weight ratio of 60:6:3:4:6; mixing the weighed solvent and dispersant with the manganese zinc ferrite precursor particles and zirconium balls for 8 hours, then adding the weighed plasticizer and glue and continuing to ball mill for 15 hours, and then casting into a 18 μm cast sheet, which was then cut into 10 0mm*100mm slices; press one side of the slices at 600℃ in an atmosphere with a nitrogen and oxygen volume ratio of (79:21) for 4 hours, then heat it to 1000℃ in a nitrogen atmosphere for 8 hours, then heat it to 1160℃ at a heating rate of 2℃ / min in an atmosphere with a nitrogen and oxygen volume ratio of (94:6) and sinter it at this atmosphere and temperature for 6 hours, and then cool it under equilibrium oxygen partial pressure to obtain manganese-zinc ferrite material.
[0155] Test Case
[0156] After the manganese-zinc ferrite materials prepared in the examples and comparative examples were subjected to a split test, μ' and μ" were measured using an Agilent E4991A impedance analyzer; the results are shown in Table 1.
[0157] Table 1
[0158]
[0159]
[0160] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the protection scope of the invention.
Claims
1. A manganese-zinc ferrite material, characterized in that: Raw materials include main ingredients and auxiliary ingredients; The main components include 52.0-53.0 mol% of Fe2O3, 18.0-19.0 mol% of ZnO, and 28.0-29.5 mol% of MnO; Based on the total weight of the main components: the auxiliary components include 100-2000 ppm Co2O3; 100-2000 ppm Bi2O3; 100-2000 ppm MoO3.
2. A method for preparing the manganese-zinc ferrite material according to claim 1, characterized in that: The steps include: (1) mixing the main component and the auxiliary component in the raw materials, pre-sintering, and first ball milling to obtain a manganese-zinc ferrite mixture; (2) mixing the manganese zinc ferrite mixture with a binder, granulating, and sieving to obtain manganese zinc ferrite precursor particles; (3) mixing the solvent, dispersant, manganese zinc ferrite precursor particles, plasticizer and glue, and then performing tape casting and sintering to obtain the manganese zinc ferrite material; The main components include 52.0-53.0 mol% of Fe2O3, 18.0-19.0 mol% of ZnO, and 28.0-29.5 mol% of MnO; Based on the total weight of the main components: the auxiliary components include 0 to 2000 ppm Co2O3; 100 to 2000 ppm Bi2O3; and 100 to 2000 ppm MoO3.
3. The method for preparing the manganese-zinc ferrite material according to claim 2, characterized in that: In step (1), the pre-sintering temperature is 700-850° C. and the pre-sintering time is 2.5-3.5 h. Preferably, the particle size of the manganese-zinc ferrite mixture is SMD 1.05-1.2 μm; Preferably, the first ball milling time is 2-3 h.
4. The method for preparing the manganese-zinc ferrite material according to claim 2 or 3, characterized in that: In step (2), the mass ratio of the manganese-zinc ferrite mixture to the binder is 1:(0.06-0.09); Preferably, the adhesive comprises polyvinyl alcohol; Preferably, the particle size of the manganese zinc ferrite precursor particles obtained after sieving is SMD3.05-5.6 μm.
5. The method for preparing the manganese-zinc ferrite material according to any one of claims 2 to 4, characterized in that: In step (3), the mass ratio of manganese zinc ferrite precursor particles, solvent, dispersant, plasticizer and glue is (50-70): (5.5-7.5): (2.5-3.5): (3.5-4.5): (5.5-7.5); Preferably, the process of mixing the solvent, dispersant, manganese zinc ferrite precursor particles, plasticizer and glue is to perform a second ball milling on the solvent, dispersant and manganese zinc ferrite precursor particles, and then add the plasticizer and glue to perform a third ball milling.
6. The method for preparing the manganese-zinc ferrite material according to any one of claims 2 to 5, characterized in that: The solvent is selected from at least one of methanol, ethanol and acetone; Preferably, the dispersant is selected from at least one of triolein and fish oil; Preferably, the plasticizer is selected from at least one of dibutyl phthalate, polyethylene glycol, and glycerol; Preferably, the glue is selected from at least one of polymethyl methacrylate and polyvinyl butyral; Preferably, the second ball milling time is 4-8h; Preferably, the third ball milling time is 12-24 hours.
7. The method for preparing the manganese-zinc ferrite material according to any one of claims 2 to 6, characterized in that: The thickness of the cast sheet obtained by tape casting is 18-40 μm; Preferably, the process of cutting is also included after tape casting and before sintering; Preferably, the cut cast sheet is a rectangle with a length of 50-150 mm and a width of 50-150 mm; Preferably, during the sintering process in step (3), the cast sheet is pressed on one side; Preferably, the sintering atmosphere in step (3) comprises nitrogen and oxygen, wherein the oxygen content in the sintering atmosphere is 3 to 21 vol%; Preferably, in step (3), the sintering temperature is 1000-1200°C; Preferably, in step (3), the sintering process is to first heat the temperature to the first temperature, and then heat the temperature to the second temperature and keep it for 2-6 hours; Preferably, in step (3), the first temperature is 1000-1100° C., and the second temperature is 1130-1200° C.; Preferably, the heating rate from the first temperature to the second temperature is 1.5-3°C / min.
8. The method for preparing the manganese-zinc ferrite material according to any one of claims 2 to 7, characterized in that: In step (3), after tape casting and before sintering, a pre-sintering process is also included; the pre-sintering process is pre-sintering at 550-650° C. for 2-4 hours; the pre-sintering atmosphere includes nitrogen and oxygen, wherein the oxygen content in the sintering atmosphere is 19-21 vol%; Preferably, the heating process from the preliminary sintering temperature to the first temperature is 6-8 hours; the atmosphere during the heating process is nitrogen.
9. The method for preparing the manganese-zinc ferrite material according to any one of claims 2 to 8, characterized in that: The step (3) further includes a cooling process after sintering, and the cooling process is carried out under a balanced oxygen partial pressure.
10. A wireless charging device, characterized in that: The wireless charging device comprises the manganese-zinc ferrite material according to claim 1 or the manganese-zinc ferrite material prepared by the preparation method of the manganese-zinc ferrite material according to any one of claims 2-9.
Citation Information
Patent Citations
High-permeability, high-frequency, high-impedance and high-Curie-temperature manganese-zinc ferrite material and preparation method thereof
CN112321293A
Submicron ceramic dielectric powder tape casting slurry as well as preparation method and application thereof
CN118598673A
Ferrite sintered body
JP2014080344A
HEAT-RESISTANT HIGH MAGNETIC PERMEABILITY MnZn FERRITE
JP2020132501A
Cited By
High-mechanical-strength wide-temperature low-loss manganese-zinc ferrite, preparation method and application thereof
CN122878124A